2011
DOI: 10.1007/s12687-011-0043-3
|View full text |Cite
|
Sign up to set email alerts
|

The impact of single gene and chromosomal disorders on hospital admissions in an adult population

Abstract: Although the role of single gene and chromosomal disorders in pediatric illness has been recognized since the 1970s, there are few data describing the impact of these often severe disorders on the health of the adult population. In this study, we present population data describing the impact of single gene and chromosomal disorders on hospital admissions of patients aged 20 years and over in Western Australia between 2000 and 2006. The number, length, and cost of admissions were investigated and compared betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 19 publications
(47 reference statements)
0
13
0
Order By: Relevance
“…This suggests that health service use may be higher among people living with rare diseases compared to the general population. This claim is supported with a study by Dye et al (2011) which found that adults living with rare genetic disorders had increased numbers of hospital admissions and longer lengths of stay [ 38 ]. Thus the health system costs attributable to rare diseases may be disproportionately high compared to the size of the population living with rare diseases.…”
Section: Discussionmentioning
confidence: 57%
“…This suggests that health service use may be higher among people living with rare diseases compared to the general population. This claim is supported with a study by Dye et al (2011) which found that adults living with rare genetic disorders had increased numbers of hospital admissions and longer lengths of stay [ 38 ]. Thus the health system costs attributable to rare diseases may be disproportionately high compared to the size of the population living with rare diseases.…”
Section: Discussionmentioning
confidence: 57%
“…Mr Kim Snowball, Director General of the Department of Health in Western Australia then launched the Symposium by highlighting the importance of rare diseases within the context of health service delivery [2,3]. He spoke of the impact of chronic, often life-shortening and generally debilitating diseases and the frequent associations with other co-morbidities such as developmental delays, depression and intellectual disability [4-6].…”
Section: Introductionmentioning
confidence: 99%
“…The ICD-10-AM coding system itself has some limitations. Previously, we reported that the ICD-10-AM code for muscular dystrophy (G710) includes early and late onset disorders, with variable modes of inheritance (Dye et al, 2011b). In addition, the data linkage methods for this study only detected cases where both family members were hospitalized during the study period and the condition of interest was documented on all admission records.…”
Section: Brameld 11mentioning
confidence: 99%